The Effect of Applying Experience Text Relationship Method on the Students’ Reading Comprehension - Juwita Purnama Sari and Berlin Sibarani (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study was aimed at finding out The Effect of Applying ETR(Experience Text Relationship) Method on the Students’ ReadingComprehension. This study used experimental design. The sample was 50% of thetenth grade of Madrasah Aliyah Swasta PPM Babussalam in academic 2012/2013.60 students of the two classes were chosen as the representative of the population.They were divided into two groups. The first group (experimental group) wastaught by using Experience Text Relationship Method and the second group(control group) was taught by using conventional method. The tests consisted oftwo types; they are pre-test and post-test. The instrument of the data collectionwas multiple choices test consisting of 25 items. The data were analyzed by usingt- test formula. The result of the data analysis showed that t- observed was 5.35and t-table was 2.00 (p = 0.05). It means t-observed was higher than t-table (tobserved= 5.35 > t-table = 2.00 ; p = 0.05). It proved that there was a significanteffect of applying experience text relationship method on the students’ readingcomprehension.